Collaborative Design Rationale and Social Creativity in Cultures of Participation - Fischer, Gerhard; Shipman, Frank (Human Technology, 2011)
The rise in social computing has facilitated a shift from consumer cultures, focused on producing finished media to be consumed passively, to cultures of participation, where people can access the means to participate actively in personally meaningful problems. These developments represent unique and fundamental opportunities and challenges for rethinking and reinventing design rationale and creativity, as people acclimate to taking part in computer-mediated conversations of issues and their solutions. Grounded in our long-term research exploring these topics, this paper articulates arguments, describes and discusses conceptual frameworks and system developments (in the context of three case studies), and provides evidence that design rationale and creativity need not be at odds with each other. Coordinating and integrating collective design rationale and social creatively provide new synergies and opportunities, particularly amid complex, open-ended, and ill-defined design problems requiring contributions and collaboration of multiple stakeholders supported by socio-technical environments in cultures of participation.